Processos oxidativos avançados: uma breve revisão - Ferreira de Jesus, Maria Fernanda (2021)
The world population corresponds to approximately 7.2 billion of people, with about 7 million being add to this number each month. Accelerated population growth drives industrial and economic development, generating new products and services that meet demands. The great concern of environmentalists is to achieve sustainable development, as the largest number of industries, especially the textile, food, pharmaceutical and pesticide sectors, end up considerably increasing the chemical residues that, if not properly treated, can contaminate the environment, with serious consequences for aquatic systems, and even for animals and humans. Considering the environmental issue, waste treatment methods are indispensable and need to be used in chemical industries of different segments, excluding or minimizing their negative impacts due to the generation of toxic by-products. Basically, effluent treatment methods can be divided into conventional methods and advanced oxidation processes. This work sought to bring together the main chemical waste treatment methods, based on their characteristics, advantages, disadvantages and applicability.